(untitled) (Journal Edutama Multidisciplinary Indonesian, 2024)
The purpose of this Community Service (PKM) by College Students is to provide an introduction and training on Microsoft Office applications to the students of SDN Lemahduhur as preparation for the Computer-Based National Assessment (ANBK). This training covers the use of Microsoft Word, Excel, and PowerPoint, which are considered essential in supporting students’ digital skills during the ANBK implementation. The method used is a practical approach, providing direct training to students through tutorial sessions and application-based practice exercises. The results of this activity show an improvement in students’ ability to operate Microsoft Office software, as well as an increase in their confidence in facing computer-based exams. With mastery of these applications, it is expected that students will be better prepared and more optimal in participating in the ANBK.